Relationships between caused by Kozyavkin© method changes in parameters of manual function and electroencephalogram, heart rate variability as well as gas discharge visualization in children with spastic form of cerebral palsy - Babelyuk, Valeriy Y.; Dubkova, Halyna I.; Korolyshyn, Tetyana A.; Mysula, Igor R.; Popovych, Dariya V.; Popovych, Igor L.; Zukow, Walery (Journal of Education, Health and Sport, 2018)
Background. Earlier we reported that in children with spastic forms of cerebral palsy (SFCP) after two-week course of rehabilitation by Kozyavkin© method reducing neural component of muscle tone (NCMT) stated in 79,3% cases while in 13,8% cases changes were not detected and in 2 children it increased. We hypothesized that such a variety of changes in NCMT is due to ambiguous changes in the background activity of the nerve centers. Aim: analysis of relationships between changes (Ch) in NCMT as well as manual functional tests, on the one hand, and parameters of EEG, HRV as well as Gas Discharge Visualization (GDV), on the other hand. Material and research methods. The object of observations were 14 children (6 girls and 8 boys) aged 8÷15 years with SFCP. State motor development at GMFCS was on II÷IV level. Functional status of the hand with MACS was at II÷III level. The estimation of hand function carried out by Dynamometry (D), Box and Block Test (B&B) and Nine Hole Peg Test (NHP). We registered also NCMT by device “NeuroFlexor” (Aggero MedTech AB, Sweden), HRV and EEG simultaneosly by hardware-software complex “Cardiolab+VSR” and “NeuroCom Standard” respectively (KhAI Medica, Kharkiv, Ukraine) as well as GDV by “GDV Chamber” (“Biotechprogress”, St-Pb, RF). Results. After two-week course of rehabilitation at 9 children NCMT reduced from 19,8±3,4 to 12,3±2,8 Newtons (Ch: -7,5±2,0 N), at 3 children NCMT taked 8,2±3,3 before and 7,9±3,5 after rehabilitation (Ch: -0,3±0,3 N) while at one girl NCMT increased from 15,1 to 17,9 N and at one boy from 6,1 to 19,4 N. Manual functional tests also changed ambiguously. The Ch in NCMT are correlated with Ch in parameters HRV&EEG (R2=0,786). The Ch in functional tests of Left hand are correlated with Ch in parameters HRV&EEG to the same extent: the level of R2 is for D 0,799, for NHP 0,773 and for B&B 0,708. Instead, for the Right hand, the correlation is stronger: R2 is 0,973, 0,792 and 0,978 respectively. As regards GDV parameters, connections are weaker, but they are also stronger for the Right hand: R2 is 0,706 vs 0,462 for B&B and 0,679 vs 0,405 for NHP but not for D (0,719 and 0,709). The Ch in NCMT are correlated with Ch in parameters GDV also weaker (R2=0,556). In its turn, changes in GDV parameters are very closely related to changes in parameters of both HRV (R2=0,999) and EEG (R2=0,998).Conclusion. In children with spastic forms of cerebral palsy caused by Kozyavkin© method changes in manual functional tests and neural component of muscle tone are determined by changes in parameters of EEG and HRV as well as GDV.